Utilization Of Waste Glass Material In Asphalt Concrete-Wearing Course (Acwc) As A Substitute For Fine Aggregate - Muhammad Taufik Habibillah Ibnu Ahmad; Helyanto Helyanto; Sarpawi Sarpawi; Robert Robert (Journal of Social Research, 2025)
Sustainable development encourages the use of waste as an alternative material in infrastructure, including on road pavement. This study evaluated the performance of Laston Coated Wear (AC-WC) asphalt mixture with the substitution of glass waste as fine aggregates in variations in 0%, 10%, 20%, and 30% levels. Material characteristics testing as well as Marshall tests and residual stability were carried out referring to the General Specification of Highways Division 6 of 2018 Revision 2. The results show that the glass waste meets the technical specifications as a fine aggregate. Blends with 10% glass content produce the highest Marshall stability value of 93.4% and the best overall performance. The Optimum Asphalt (KAO) content has increased as the glass content has increased, but it remains below the normal mix KAO. Mixing with glass also shows good water resistance. Therefore, a 10% glass waste substitution is recommended as an alternative to fine aggregates in AC-WC mixtures to support environmentally friendly road infrastructure.